Heavy metals pollution in children playgrounds - an environmental modelling and statistical analysis - Šapčanin, Aida; Čakal, Mirsada; Ramić, Emina; Smajović, Alisa; Pehlić, Ekrem (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
Models could be used to simulate target variable responses to changes in very complex systems such as soils polluted by heavy metals. Chemical properties of soil such as pH in H2O, pH in 1 mol/L KCl, humus and CaCO3 could influence metal mobility and can be used to assess impact of various antropogenic activities. The soil samples were collected from playgrounds located in different areas of Sarajevo. Heavy metals: Cd, Pb, Cu and Zn and basic chemical properties of soil were determined. Statistical analysis was conducted to obtain the correlation coefficient of two selected variables in a data sample, as a normalized measurement of how the two are linearly related. Determined content (mg/kg) for Cd, Pb, Cu and Zn in the spring season were in the ranges of: 0.91-2.15; 26.69-118.97; 19.14-80.21; 75.85-161.45 and in the autumn season were in the ranges of: 0.80-2.14; 41.07-152.71; 29.46-140.74; 71.77-199.04, respectively. The results showed that the highest correlation coefficient was 0.91, for the total content of Cu in the soils in regard to the content of Pb in the autumn season and this indicates a strongand positive correlation. Generally, our results could be used for prediction of heavy metal distribution in playground soil.